Gendering Marine Conservation: The Politics of Marine Protected Areas and Fisheries Access - Baker-Médard, Merrill (Society & natural resources, 2017)
Drawing on ethnographic case studies from Madagascar, this research shows that multiple marine conservation projects have institutionalized inequitable access to marine recourses along gendered lines. Despite discursive and institutional shifts toward more "collaborative" and "community-based" conservation programing, there is a deficiency of women's nominal as well as effective participation in community management organizations. This research shows that conservation organizations' focus on proximate drivers of marine resource use, or a politics of picking the "low-hanging fruit," over ultimate drivers such as global commodity chains, places disproportionate emphasis on marine spatial enclosures and restricting specific, and gendered, harvest methods. To address gender bias concerning access to and control over natural resources, we must go beyond the rhetoric of "community involvement" to address gendered inequalities in conservation decision making, and whose interests are served by conservation projects.